Салон медвежьих услуг: Повесть / Г. М. Куликова - Куликова Галина Михайловна (Шоу-детектив, 2003)
Экземпляры: 6 (20170412) / Инвентарный номер: 49390 / Цена: 60.00 / Авт.знак: К 90 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6